PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SD INPRES BORISALLO KECAMATAN PARANGLOE KABUPATEN GOWA - Tahir, Masdiana; Suhaenah, Asriani; Aminah, Aminah (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
The village of Borisallo is a Development Partner Village of UMI in Gowa Regency. One of theeducational facilities is SD Inpres Borisallo where a school is a place of learning that can be athreat of disease transmission if it is not managed properly. Problems with children's healthbehavior are usually related to personal and environmental hygiene. By that, the planting of valuesof health behavior in elementary schools is an absolute necessity and an effort to realize "Healthyand Independent Community" as contained in the health profile of Gowa Regency. As for studentsin SD Inpres Borisallo as many as 102 children with 9 teaching staff. Ideally, the health ofelementary school children is monitored by UKS, but due to various limitations, the role of theUKS SD Inpres Borisallo has not been implemented optimally and there is no special handwashing place for students. The target to be achieved is to increase students' knowledge,awareness, willingness and ability to live clean and healthy lives, and be expected to play an activerole in realizing optimal health degrees, instilling clean and healthy behavioral values (PHBS),improving the practice of handwashing with soap true and became a habit in the daily lives of SDInpres Borisallo students. The approach taken to achieve the target is to provide clean and healthylife behavior counseling (PHBS) and socialization of how to wash hands with soap properly andcorrectly, procure posters on how to wash hands and procure water tap pipe installationinfrastructure for hand washing needs in SD Inpres Borisallo students.